“Shifting in” state sovereignty: social policy and migration control in Costa Rica - Voorend, Koen (2014)
This paper challenges the globalist claim that nation states lose sovereignty to normative frameworks of international human rights with regards to their migration policy. In contrast, the analysis of the interplay between migration and social policy in Costa Rica shows that states may find inventive ways to maintain control over its migration policy and remain central in the granting of social rights to immigrants and their actual access to social policy. Indeed, Costa Rica has shifted in its migration control, by giving the country’s emblematic and praised social security and healthcare institution, the Caja Costarricense de Seguro Social, a pivotal role in immigrants’ regularization process, thereby creating barriers to healthcare benefits for immigrants. As such, the state remains central in processes of social integration, while citizenship and migratory status continue to be key determinants for immigrants’ access to national welfare benefits